Pengaruh Koordinasi Dan Sarana Prasarana Terhadap Prestasi Kerja Pegawai Bidang Sarana Prasarana Transportasi Dinas Perhubungan Kota Surabaya - Suhartono, Suhartono; Krishnawan, Reo; Anwar Arifin, Mohamad Sabiqul; Winarsih, Tutik (Universitas Pahlawan Tuanku Tambusai, 2024)
Infrastructure such as roads, clean water, sanitation, markets, terminals, etc. must be balanced with the needs of the community itself, otherwise it will have negative effects that are detrimental to the community. This research is to determine the influence of Coordination and Infrastructure on the Work Performance of Employees in the Transportation and Infrastructure Sector of the Surabaya City Transportation Service. In accordance with the results of this research, several things can be concluded, including: Factors consisting of Coordination and Infrastructure have a significant influence simultaneously on the work performance of employees in the Transportation Facilities and Infrastructure Sector of the Surabaya City Transportation Service, Surabaya City. The factors consisting of Coordination and Infrastructure have a significant influence partially on the work performance of employees in the Transportation Infrastructure Sector of the Surabaya City Transportation Service, Surabaya City. Among the factors consisting of Coordination and Infrastructure, it turns out that coordination has a dominant influence on the work performance of employees in the Transportation Infrastructure Sector of the Surabaya City Transportation Service, Surabaya City, with a partial influence of 56.8%. As input, suggestions can be given that can be proposed for improving management in organizations in the Transportation Infrastructure Sector of the Surabaya City Transportation Department, Surabaya City.